Melatonin Attenuates Intervertebral Disk Degeneration via Maintaining Cartilaginous Endplate Integrity in Rats - Wu, Xiexing; Liu, Yijie; Du, Jiacheng; Li, Xiaoping; Lin, Jiayi; Ni, Li; Zhu, Pengfei; Zhou, Hong; Kong, Fanchen; Yang, Huilin; Geng, Dechun; Mao, Haiqing (Frontiers in Physiology, 2021)
Objective: The aim of this study is to verify whether melatonin (Mel) could mitigate intervertebral disc degeneration (IVDD) in rats and to investigate the potential mechanism of it. Method: A rat acupuncture model of IVDD was established with intraperitoneally injection of Mel. The effect of Mel on IVDD was analyzed via radiologic and histologic evaluations. The specific Mel receptors were investigated both in nucleus pulposus (NP) and cartilaginous endplates (EP). In vitro, endplate cartilaginous cells (EPCs) were treated by different concentrations of Mel under LPS and Luzindole condition. In addition, LPS-induced inflammatory response and matrix degradation following nuclear factor kappa-B (NF-κB) pathway activation were investigated to confirm the potential mechanism of Mel on EPCs. Results: The percent disc height index (%DHI) and MRI signal decreased after initial puncture in the degeneration group compared with control group, while Mel treatment protected disc height from decline and prevented the loss of water during degenerated process. In the meantime, the histological staining of Mel groups showed more integrity and well-ordered construction of NP and EP in both low- and high-concentration compared with it in degeneration group. In addition, more deep-brown staining of Coll-II was showed in the Mel groups compared with it in the degeneration group. Furthermore, in rat samples, immunohistochemical staining showed more positive cells of Mel-receptor 1a and 1b in EP, instead of in the NP. Moreover, evident osteochondral lacunae formation was observed in rat EP in degeneration group, after Mel treatment, the osteochondral destruction alleviated accompanying fewer receptor activator for nuclear Factor-κB ligand (RANKL) and tartrate resistant acid phophatase (TRAP)-stained positive cells expressed in the EP. In vitro, Mel could promote the proliferation of EPCs, and that, protected EPCs from degeneration under LPS treatment. What’s more, Mel downregulated the inflammatory response and matrix degradation of EPCs activated by NF-κB pathway through binding to its specific receptors. Conclusion: These results indicate that Mel protects the integrity of EP and attenuates IVDD by binding to the melatonin-receptors in EP. It may through alleviating the inflammatory response and matrix degradation of EPCs activated by NF-κB pathway.